Antifungal activity of umbelliferone derivatives: Synthesis and structure-activity relationships. (March 2017) - Pan, Le; Li, Xiuzhuang; Jin, Hui; Yang, Xiaoyan; Qin, Bo
Abstract: Umbelliferone was an important allelochemical with a wide spectrum bioactivity. In our previous study, C7 hydroxy in the backbone of umbelliferone was identified to be responsible for its phytotoxicity and the targeted modification of the above site could lead to the phytotoxicity loss. In view of this, a series of hydroxycoumarins and C7 O-substituted umbelliferone derivatives were efficiently synthesized to evaluate their antifungal activity against four phytopathogenic fungi. Most of them, as we predicted, exhibited improved fungicidal activity. The phytotoxicity of effective compounds was also assayed by Lactuca sativa to investigate their side effects on plant growth. Compounds9 and17 were identified to show strong antifungal activity with low phytotoxicity. A brief investigation on structure-activity relationships revealed that the modification at the C7 hydroxy of umbelliferone could be a promising way to enhance the antifungal activity with decreasing the phytotoxicity. Graphical abstract: Highlights: Natural compound derived fungicides discovery. Targeted modification and synthesis of umbelliferone. Enhanced antifungal activity with low phytotoxicity. Providing meaningful tactics for the further development of umbelliferone-related fungicides.